An Updated List of Neuromedicinal Plants of Pakistan, Their Uses, and Phytochemistry. (3rd March 2019) - Khan, Abdul Waheed; Khan, Arif-ullah; Shah, Syed Muhammad Mukarram; Ullah, Aziz; Faheem, Muhammad; Saleem, Muhammad
Abstract : Background. Almost every region of Pakistan is stacked with a large number of medicinal plants. Due to high cost and unavailability of allopathic medicines for the neurological diseases, especially in rural areas, traditional healers prescribe phytotherapy for various neurological diseases like epilepsy, depression, anxiety, insomnia, Alzheimer, and migraine. Such treatments are considered to be most effective by the native people. Methods. The data was collected from articles published on medicinal plants of various districts of Pakistan, using article search engines like Medline, Pubmed, Web of Science, Science Direct, and Google Scholar. Also, information regarding various neurological uses and mode of applications of medicinal plants was obtained from traditional healers, folk medicine users, and local elderly people having knowledge of medicinal plants. Results. A total of 54 families were found to be used in various neurological diseases, of which the highest use was of Solanaceae (22.22%), Asteraceae (12.96%), Lamiaceae, Papaveraceae, and Poaceae, 9% each, and Caprifoliaceae, Cucurbitaceae, Rhamnaceae, and Rosaceae, 5.5% each. According to districts, 15% of plants that were effective in neurological affections were found in Bahawalpur, 11% in Swat, 8% in Muzaffarabad, 7% in Malakand, and 6% in Bahawalnagar, Dir, Gilgat, and Sarghoda each, with 5% in Dera ghazi khan and Jhelum each. According to the plant's habit, out of total of 103 plants, 61.15% were found to be herbs, 22.33% trees, 11.65% shrubs, and 4.85% climbers. According to the part used of plant, whole plant, leaves, fruits, roots, seeds, and flowers were found to be used 32.03%, 24.27%, 20.38%, 16.50%, 13.59%, and 11.65%, respectively. According to disease's types, 45.63% were found to be effective in insomnia, 31.06% in epilepsy 12.62% in depression, 6.80% in anxiety, 7.77% in hysteria, and 5.88% in migraine. Conclusion. Taking into consideration this useful knowledge on medicinal properties of the plants for curing neurologic diseases, it is believed that research in areas of ethnomedicine and ethnopharmacology can bring auspicious results that have potential of adding value to the very rich natural resources of Pakistan. This study will help all the researchers from diverse backgrounds working on plants based medicine for neurological diseases.